A smarter way to use your smartphone: an intervention to limit smartphone-related distractions reduces hyperactivity but not inattention symptoms - Wasmuth, Julian; Reinhard, Iris; Hill, Holger; Alpers, Georg W.; Shevchenko, Yury; Kiefer, Falk; Leménager, Tagrid (European addiction research, 2022)
Introduction: Smartphones are often helpful in our everyday lives. Yet, they also tend to interrupt us during other activities. It has been argued that such distractions contribute to attention-deficit/hyperactivity disorder-like symptoms. However, since there are mostly correlational studies, the causal nature of this relationship is unclear. Our aim was to test whether reducing smartphone-related distractions might have a beneficial effect on inattention and hyperactive symptoms. Methods: We conducted a 1-week field experiment with 37 healthy undergraduates and quasi-randomly assigned them to an intervention or control group (CG). The intervention group was given theory-based specific instructions that aimed at reducing smartphone-related distractions, whereas the CG received no intervention. The outcomes of interest were inattention level, hyperactive symptoms, and working memory accuracy. Results: Compared to those in the control condition, participants who limited their smartphone use showed considerable reductions in hyperactive symptoms after 1 week - particularly those who displayed high problematic smartphone use. However, there were no group differences regarding inattention symptoms and working memory accuracy. Discussion: The results give a first hint that strategically reducing smartphone-related distractions via specific but simple use modifications can mitigate hyperactive symptoms. Especially people with problematic smartphone use seem to profit from such an intervention. Remaining questions and directions are discussed.
Gesehen am 04.08.2022